Xenograft Models for Preclinical Assessment of Anticancer Therapies: A Comprehensive Review - Ebrahim sadaqa; Muhammad Ikhlas Arsul (Ad-Dawaa: Journal of Pharmaceutical Sciences, 2023)
Introduction: Xenograft models play a pivotal role in preclinical studies for assessing the efficacy of anticancer medications. In this comprehensive review, we present an overview of current advancements and future prospects in xenograft research, focusing on their significance in guiding drug development and clinical translation. Aim: Our aim is to conduct an in-depth review of xenograft models, their utility in evaluating anticancer drug effectiveness and ultimately improve patient outcomes. Methods We conducted an in-depth literature search using databases such as ScienceDirect, Google Scholar and PubMed with keywords including "xenograft model, cancer CDX PDX." We then reviewed and analyzed relevant studies that utilized xenograft models in order to highlight key findings and contributions made through such models. Results: Our analysis showcases the essential role of xenograft models in assessing the efficacy of anticancer drugs. We discuss the benefits and limitations of these models, emphasizing their importance in guiding drug development and clinical decision-making. Conclusion: Xenograft models remain invaluable tools in preclinical cancer research despite their inherent limitations, with researchers continually striving to refine and enhance these models to ensure their reliability in an ever-evolving field of cancer therapeutics. Utilizing xenograft models allows researchers to evaluate anticancer drug activity more accurately while striving for improved patient outcomes.